2019
DOI: 10.2478/zireb-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Firm Financial Status and Investment Behaviour: Evidence from Manufacturing Firms in Nigeria

Abstract: The study examines firm’s investment behaviour sensitivity to cash flow before, during and after the recent global financial crisis using the data of 28 firms listed on the Nigerian Stock Market during the period from 2001 to 2012. The contribution of the study to the existing literature rests on using financial crisis as basis for classifying firms as either financially constrained or unconstrained. Employing the panel data and instrumental variable estimation techniques, the study finds that firms’ investmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
2
1
0
Order By: Relevance
“…Therefore, it supports the widely held argument that institutions play a significant role in promoting long-run growth. This finding corroborates previous studies such as Aminu et al (2019) and Chinn and Ito (2006) which suggest that institutions can promote or diminish the prospect of the industrial sector in an economy.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it supports the widely held argument that institutions play a significant role in promoting long-run growth. This finding corroborates previous studies such as Aminu et al (2019) and Chinn and Ito (2006) which suggest that institutions can promote or diminish the prospect of the industrial sector in an economy.…”
Section: Resultssupporting
confidence: 92%
“…The finding also implies that instead of finance and institutional factors complementing each other in the development process of industrialization, they are substitutes to each other in the process, and it is consistent with that of Ahlin and Pang (2008), Berhane (2018) and Olaniyi and Oladeji (2020) which found that the interaction of finance and institutions inhibit growth and that both FD and institutional factors are substitutes in the process of economic growth. More specifically, this result agrees with the study by Aminu et al (2019) in the case of Nigeria, which found that FD promotes manufacturing output and that the beneficial impact of FD is moderated downwards by institutional factors which comprise bureaucratic quality, democratic accountability and corruption control. However, the result contradicts the result in several studies that institutions enhance the financial system to increase growth and that both FD and institutional factors are complements in the economic growth process (Demetriades and Law 2006;Gazdar and Cherif 2015;Law et al 2018;Olaniyi and Adedokun 2022).…”
Section: Resultssupporting
confidence: 91%
“…By performing these functions, financial markets engender capital accumulation and technological innovation that would spur economic growth (Raifu & Afolabi, 2022). Given these theoretical connections between financial development and economic growth, several studies have examined the influence of financial development on economic growth including other areas of the economy such as investment, total factor productivity, sectoral performance, trades, poverty and inequality, even though empirical findings appear to be mixed (Valickova et al, 2015;Isah and Soliu, 2016;Muyambiri and Odhiambo, 2018;Ni and Liu, 2019;Aminu et al, 2019aAminu et al, , 2019bRaifu & Folarin, 2020;Adeboje et al, 2021, Afolabi, 2022.…”
Section: Introductionmentioning
confidence: 99%